Real-Time Temperature Control for High Arch Dam Based on Decision Support System - 井向阳 刘杏红 周伟 常晓林 (Transactions of Tianjin University, 2014)
It is important and difficult to control the temperature of mass concrete structure during high arch dam construction.A new method with decision support system is presented for temperature control and crack prevention.It is a database system with functions of data storage,information inquiry,data analysis,early warning and resource sharing.Monitoring information during construction can be digitized via this system,and the intelligent analysis and dynamic control of concrete temperature can be conducted.This method has been applied in the construction of the Dagangshan Arch Dam in China and has proven to be very convenient.Based on the decision support of this system and the dynamic adjustment of construction measures,the concrete temperature of this project is well-controlled.